2022
DOI: 10.3991/ijim.v16i07.25739
|View full text |Cite
|
Sign up to set email alerts
|

Android-Based Interactive Media to Raise Student Learning Outcomes in Social Science

Abstract: Learning media is one of the important components in the process of implementing learning, especially during the current pandemic. But in reality there are still few teachers who use media in the learning process, causing student learning outcomes to decline. Interactive media which is one of the media that can be used to attract students' attention by combining systems ranging from text, images, videos, and audio/sound can provide new experiences for students in learning. This study aims to determine student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Students can dig up information about the material provided through digital media to increase students' curiosity about the material. Because it is fun learning experience, student achievement also experienced a significant increase [3].…”
Section: Resultsmentioning
confidence: 99%
“…Students can dig up information about the material provided through digital media to increase students' curiosity about the material. Because it is fun learning experience, student achievement also experienced a significant increase [3].…”
Section: Resultsmentioning
confidence: 99%
“…Every year AbL becomes an interesting research idea, and its development begins to be considered by researchers, especially in the field of Education. AbL is deemed to have the feasibility and flexibility of learning [54] and is a renewable idea in this era of globalization [55]. The WbL trend decreased in 2015 and became an uptrend again until 2021.…”
Section: Research Trend Of Abl and Wbl During Ten Last Yearmentioning
confidence: 99%
“…Furthermore, utilizing this application increases students' attention and makes it simpler for them to learn the topic. The findings revealed that interactive media based on Android had a beneficial influence on student learning outcomes (Sujarwo et al, 2022). Figure 1 shows Android's dominance in major nations such as India, Brazil, China, and Germany.…”
Section: Introductionmentioning
confidence: 98%